Predicting 1‐year heart failure hospitalization and mortality post‐discharge from the intensive cardiac care unit - Andreas Bugge Tinggaard; Solenn Toupin; Jean Guillaume Dillinger; Clément Delmas; Antonin Trimaille; Claire Bouleti; Guillaume Schurtz; Charles Fauvel; Jean Claude Dib; Stéphane Andrieu; François Roubille; Thomas Levasseur; et al. (ESC Heart Failure)
Abstract Aims Despite the high risk of rehospitalization for heart failure (HF) and death among patients admitted to the intensive cardiac care unit (ICCU), no accurate prediction score for these outcomes exists. We aimed to develop a risk score to predict unplanned HF hospitalization and death 1‐year post‐discharge in an unselected cohort of patients admitted to the ICCU. Methods Based on a national, multicentre study, we included all consecutive patients admitted to the ICCUs in 39 French centres from 7 to 22 April 2021. We randomly selected a training cohort of 21 centres (n = 1008) to develop the ICCU‐HF score and a validation cohort of eight other centres (n = 463). The primary composite outcome was unplanned hospitalization for HF and cardiovascular death at 1‐year follow‐up after discharge. Using the score, patients were stratified into three risk groups to evaluate the prognostic value. Results Using a least absolute shrinkage and selection operator (LASSO) regression approach, we identified seven predictors: left ventricular ejection fraction, significant valvular disease grade 2+, Killip score >1, NT‐proBNP, creatinine level, previous ventricular arrhythmia and use of inotropes during hospitalization. In 1471 patients (63 ± 15 years, 70% men), 99 (6.7%) experienced the primary outcome. The ICCU‐HF score outperformed NT‐proBNP, the strongest individual predictor (area under the curve [AUC] 0.77, 95% CI [0.71–0.83] vs. AUC 0.72, 95% CI [0.66–0.79], P = 0.008), demonstrating excellent performance with an AUC of 0.83 (95% CI: 0.77–0.89) to predict outcomes in the validation cohort. Compared with the low‐risk group, the intermediate‐risk and high‐risk groups had significantly higher risks of the composite outcome (HR 4.09, 95% CI [2.23–7.50], P < 0.001 and 12.69, 95% CI [7.02–22.95], P < 0.001), proving strong risk stratification capability of the ICCU‐HF score. Conclusions The ICCU‐HF score showed good performance in predicting the 1‐year risk of unplanned HF hospitalization and death in a large cohort of unselected patients admitted to the ICCU, with excellent results in the validation cohort. This score effectively stratifies patients into risk groups, enhancing its utility in clinical decision‐making.